2018
DOI: 10.1007/s00592-018-1153-8
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum levels of uric acid are associated with a reduced insulin clearance in non-diabetic individuals

Abstract: Higher serum levels of UA may affect insulin clearance by impairing hepatic insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…Höieggen et al [30] studied the relationship between SUA and insulin resistance in untreated borderline hypertensive young men, and they found no relationship. Other two studies conducted by Vuorinen-markkola et al [31] and Fiorentino et al [32] reported SUA was independently associated with insulin sensitivity in non-diabetic subjects, which were accorded with our results. Fiorentino et al [32] also found high SUA levels correlated with reduced insulin clearance.…”
Section: Discussionsupporting
confidence: 93%
“…Höieggen et al [30] studied the relationship between SUA and insulin resistance in untreated borderline hypertensive young men, and they found no relationship. Other two studies conducted by Vuorinen-markkola et al [31] and Fiorentino et al [32] reported SUA was independently associated with insulin sensitivity in non-diabetic subjects, which were accorded with our results. Fiorentino et al [32] also found high SUA levels correlated with reduced insulin clearance.…”
Section: Discussionsupporting
confidence: 93%
“…Through reading a large number of literature and studies, we believe that uric acid is closely related to diabetes. Poor lipid metabolism in individuals with higher UA levels may lead to increased fasting and postprandial insulin levels, high-sensitivity C-reactive protein, hepatic insulin resistance index, and decreased glomerular filtration rate and skeletal muscle insulin sensitivity; high levels of SUA may impair liver insulin sensitivity and insulin clearance [53]. Perticone F [54] was documented when hypertensive NGT ≥ 155 mmHg, and UA is closely related to 1-h postload glucose during an oral glucose tolerance.…”
Section: Epidemiology Studiesmentioning
confidence: 99%
“…Interestingly, it has been shown that UA promotes oxidative stress and vascular inflammation [11], reducing nitric oxide bioavailability thus favouring endothelial dysfunction [12]. Moreover, UA may directly affect the intracellular insulin signalling pathway, consequently inducing insulin resistance (IR) [13]. All these mechanisms may, in turn, cause subclinical organ damage, and accumulating evidence indicates that higher UA concentrations are associated with arterial stiffness (AS), a marker of vascular damage, and an independent predictor of cardiovascular (CV) events.…”
Section: Introductionmentioning
confidence: 99%